2008
DOI: 10.1002/gcc.20552
|View full text |Cite
|
Sign up to set email alerts
|

Bone morphogenic protein 3 inactivation is an early and frequent event in colorectal cancer development

Abstract: Bone morphogenic proteins (BMPs) are members of the TGFB growth factor superfamily with well-described functions in bone formation. Although disrupted BMP signalling in tumor development has more recently been investigated, a role for BMP3 in colorectal cancer (CRC) has remained largely unexplored. The aim of this study was to investigate BMP3 disruption in CRCs in relation to both the traditional and serrated pathways of tumor progression. BMP3 was down-regulated as assessed by real-time PCR in 50 of 56 prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
73
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 87 publications
(85 citation statements)
references
References 37 publications
8
73
0
Order By: Relevance
“…Although the role of BMP3 in the pathogenesis of cancer is unknown, several studies have demonstrated that BMP3 participates in the development of various types of cancer (17)(18)(19)(20)(21). Loh et al (17) reported that in colon cancer cell lines with methylation-dependent BMP3 downregulation, cell colony growth suppression was observed following the reintroduction of BMP3 coding sequences.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Although the role of BMP3 in the pathogenesis of cancer is unknown, several studies have demonstrated that BMP3 participates in the development of various types of cancer (17)(18)(19)(20)(21). Loh et al (17) reported that in colon cancer cell lines with methylation-dependent BMP3 downregulation, cell colony growth suppression was observed following the reintroduction of BMP3 coding sequences.…”
Section: Discussionmentioning
confidence: 99%
“…Loh et al (17) reported that in colon cancer cell lines with methylation-dependent BMP3 downregulation, cell colony growth suppression was observed following the reintroduction of BMP3 coding sequences. Methylation of the BMP3 promoter has also been described in subtypes of stomach (18), lung (20), pancreatic (19) and breast cancers (21) with downregulated BMP3 expression.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations